La santé des migrants internationaux dans la province d’Almería : indicateur de différenciations et d’inégalités. - Betty Rouland (L'Espace Politique)
This article aims to interpret health inequalities through a study of international migrants installed in the province of Almeria (Andalusia, Spain). Based on intensive greenhouse agriculture and the service sector (tourism), the regional economic system produces and juxtaposes heterogeneous, sometimes even contradictory, migratory modes, intrinsically linked to the dynamics of contemporary globalization (social and (un)documented labor, retired migration). The health of migrants is used here as an indicator of differentiation processes in the contemporary world: political and administrative boundaries shift, are displaced and reorganized in places of immigration. In addition to the socioeconomic differences between the countries of origin, also politico-administrative borders exercise an even more differentiating function. This work is based on a survey amongst four main groups of migrants represented in the province (Moroccan, Rumanian, British and one aggregated group of West Africans). Moreover, participant observation in collaboration with Almeria’s Red Cross has allowed for overcoming the gap between official and real populations (Forbes & Wainwright, 2001). The analysis of the empirical data (sanitary and epidemiological data) as well as of public health policies (national, regional and local), has shown the local reconstruction of the mosaic of states in the world. As such, the health landscapes locally evolving amongst the migrants in the province of Almeria provide a mirror of global socio-economic inequalities.